THE UPCOMING PRESIDENTIAL ELECTIONS OF 2018 IN THE REPUBLIC OF MADAGASCAR: POLITICAL ANALYSIS AND FORECASTS - Andriamaharinjaka (RUDN Journal of Political Science, 2018)
The article is devoted to the upcoming presidential elections in the Republic of Madagascar, the actions of the current ruling power are subjected to analysis. Special focus was made on the ongoing political situation before the elections. The possible legal field in which could be organized the upcoming elections and its possible reforms are analyzed. Forecasts about the evolution of the political situation in the Republic were given.